REDUPLICATION WITH SOUND MODIFICATION IN INDONESIAN - Wijana, I Dewa Putu (Prosiding Seminar Nasional Bahasa Ibu, 2024)
This paper is an attempt to seek the rules regarding kinds and distribution of base forms, and sound changes, and grammatical meanings of sound modification reduplication in Indonesian. By using data primarily gathered through intuitive method  and added with ones extracted from Indonesian linguistic text books, it is found that the reduplication bases can be identifiable and unidentifiable. Identifiable base can be placed either initial or final. The sound involved can be one or more vowel as well as consonant. Reduplication with consonant sound change always places its base in initial position. Reduplication with unidentifiable base forms can involve  more than one vowels, consonant or vowel and consonant altogether. The unidentified base leads to suspect that the whole forms can be actually pseudo reduplication, or combinations double unique morphs.